OPTIMALISASI BIDAN DESA DALAM PENYEBARAN INFORMASI KESEHATAN BAGI MASYARAKAT DI KABUPATEN BANDUNG (Studi Kasus tentang Pemanfaatan Bidan Desa Dalam Penyebaran Informasi Kesehatan bagi Masyarakat di Kabupaten Bandung) - Ditha Prasanti; Ikhsan Fuady; Sri Seti Indriani (Program Studi Ilmu Komunikasi, 2018)
Village midwives are a very important source in the therapeutic communication process in rural areas. This communication process can be seen in the distribution of health information and health services provided by the local village apparatus. In this research location in Kertasari sub-district, Bandung district, the authors found one area that optimizes the role of village midwives in the dissemination of health information for the surrounding community, namely Tarumajaya village. This phenomenon is interesting to study because this condition is not necessarily found in all regions. Therefore, the author wants to explain the use of village midwives in the dissemination of health information for the community in the village of Tarumajaya. This study uses a qualitative approach to the case study method. The author also selected 4 informants who met the research criteria. The data collection techniques used are observation, in-depth interviews, and documentation studies from several literatures that are relevant to the research topic of the author. The results obtained showed that the use of village midwives in the dissemination of health information for the community in Tarumajaya village included: (1) The existence of village midwives in Tarumajaya Polindes as a credible source / communicator and very helpful in the process of distributing health information; (2) There are messages in the form of various health information delivered by village midwives through various health programs in the village; (3) The coordination of village midwives with other health workers in the nearest health center to facilitate the implementation of health programs; (4) Support from village officials in carrying out health programs; (5) Full trust given by the local community, in terms of being a communicant, to the village midwife, thus supporting the smooth process of disseminating existing health information. Keywords: Utilization, Village Midwives, Information, Health, Kertasari District, Bandung Regency